2005
DOI: 10.1271/bbb.69.31
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Protein of Korean Foxtail Millet on Plasma Adiponectin, HDL-Cholesterol, and Insulin Levels in Genetically Type 2 Diabetic Mice

Abstract: We examined the effects of intake of Korean foxtail millet protein (FMP) on plasma levels of lipid, glucose, insulin, and adiponectin in genetically type 2 diabetic KK-A y mice. When mice were fed a normal FMP diet or a high-fat-high-sucrose diet containing FMP for 3 weeks, in both experiments plasma concentrations of high-density lipoprotein cholesterol (HDL-cholesterol) and adiponectin increased remarkably in comparison with a casein diet group, whereas concentrations of insulin decreased greatly and that of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(73 citation statements)
references
References 34 publications
5
65
2
1
Order By: Relevance
“…It is also useful for people who are suffering from atherosclerosis and diabetic heart disease (Gélinas et al, 2008). Choi et al (2005) and Park et al (2008) reported that protein concentrate of Korean foxtail millet and proso millet significantly elevated plasma adiponectin and HDL cholesterol levels and caused major decreases in insulin levels relative to a casein diet in type 2 diabetic mice. Furthermore, proso millet also improved glycemic responses and plasma levels (Park et al, 2008).…”
Section: Some Potential Health Benefits Of Milletsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also useful for people who are suffering from atherosclerosis and diabetic heart disease (Gélinas et al, 2008). Choi et al (2005) and Park et al (2008) reported that protein concentrate of Korean foxtail millet and proso millet significantly elevated plasma adiponectin and HDL cholesterol levels and caused major decreases in insulin levels relative to a casein diet in type 2 diabetic mice. Furthermore, proso millet also improved glycemic responses and plasma levels (Park et al, 2008).…”
Section: Some Potential Health Benefits Of Milletsmentioning
confidence: 99%
“…In addition, proso millet protein concentrate has protective effects against D-galactosamin-induced liver injury in rats . Choi et al (2005) and Park et al (2008) concluded that proso millet protein could be a potential therapeutic intervention in type 2 diabetes. Devi et al (2011) review the nature of polyphenols and dietary fiber of finger millet and their role with respect to the health benefits associated with millet.…”
Section: Some Potential Health Benefits Of Milletsmentioning
confidence: 99%
“…Namely, other investigators showed that the protein fraction of proso millet caused protective effects on rat liver injury induced by D-galactosamine [4], and that the proteins of foxtail millet improved the plasma levels of lipid, glucose, insulin and adiponectin in diabetic mice [5]. In a separate study, an extract of Japanese rice bran showed strong antioxidant and antigenotoxic activities, and the active principle in the extract responsible for these activities was identified to be an endogenous protein, peroxidase [20].…”
Section: Discussionmentioning
confidence: 99%
“…Quelques études récentes suggèrent un effet bénéfique de la substitution des protéines animales par des protéines végétales sur certains facteurs de risques associés au syndrome méta-bolique. Ainsi, une diminution des triglycérides circulants et une augmentation du cholestérol-HDL ont été rapportées après substitution des protéines animales par des protéines de soja (Castiglioni et al, 2003 ;Greaves et al, 2000 ;Han et al, 2002 ;Lucas et al, 2001 ;Teede et al, 2001), de lupin (Sirtori et al, 2004) ou de millet (Choi et al, 2005), chez l'Homme ou chez l'animal. Chez l'Homme, une diminution de la pression artérielle a été observée en réponse à une augmentation de la consommation de protéines de soja (He et al, 2005 ;Jenkins et al, 2002).…”
Section: Potentiel Des Protéines Végétales Dans La Prévention Du Syndunclassified